Blood sugar - Rothchild, Sascha (New York : G.P. Putnam's Sons, 2022)
Although she did kill three people, an animal-loving Miami therapist with a successful practice is accused of murdering her husband, who she actually did not kill.
Keywords: Murder -- Investigation -- Fiction; Serial murderers -- Fiction; Police -- Florida -- Miami -- Fiction; Family secrets -- Fiction; Husbands -- Death -- Fiction; Thrillers (Fiction); Detective and mystery fiction